2017
DOI: 10.1007/s12032-017-1022-2
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 antigen expression in luminal A and triple-negative breast cancer

Abstract: Biomarkers for the prognosis of breast cancer have been routinely used in clinical practice, including the expression of hormone receptors, Ki-67 and HER-2. More recently, Bcl-2 has been recognized as an important prognostic factor in breast cancer, although controversies persist with respect to the significance of its expression. The aim of the present study was to evaluate Bcl-2 antigen expression in luminal A and triple-negative breast cancer. Sixty women with invasive ductal carcinoma were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
8
1
Order By: Relevance
“…Bcl-2 is recognized as an important factor with anti-apoptotic effects and was originally identified in human follicular B cell lymphoma (36). Bcl-2 expression has been revealed to be downregulated in triple-negative breast cancer (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 is recognized as an important factor with anti-apoptotic effects and was originally identified in human follicular B cell lymphoma (36). Bcl-2 expression has been revealed to be downregulated in triple-negative breast cancer (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…A consistent and strong positive correlation between Bcl-2 positivity and hormone receptor expression is reported in breast cancer, and concerns both ER and PR [7, 9, 12, 19, 49, 51, 52, 54, 55, 5860]. Bcl-2 positivity of breast cancers has been associated with a lower Ki-67 proliferation index [7, 12, 16, 50, 60], with the luminal phenotype [7], and especially the luminal-A phenotype [64]. Indeed, BCL2 is upregulated by estrogens in breast cancer cells [65], explaining why Bcl2-positive expression in breast cancer may be considered a sign of ER functional activity [7].…”
Section: Discussionmentioning
confidence: 99%
“…Osada et al suggested a relationship between CV risk assessed with SCORE chart and predicting molecular response to TKIs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%